Synthesis, Spectral Characterization And Pharmacological Significance of Fe(III) Complex With Schiff Base and Thiocyanate ION as Ligands - Govindharaju, R.; Durairaj, P.; Muruganantham, N.; Meenakshi, V. Mukil; Maruthavanan, T.; Ramachandramoorthy, T. (International Journal of Scientific Research in Biological Sciences, 2019)
A novel Fe(III) complex of Schiff’s base derived from phenylacetylurea condensed with salicylaldehyde (SBPS) and thiocyanate(SCN-) ion was synthesized by using microwave irradiation. Microwave synthesis gives high yield of the complex within a short time. The molecular formula and the probable geometry of the complex have been deduced from elemental analysis, molar conductance, UV, FT-IR, and Far IR spectra. The molar conductance indicates that the Fe(III) complex is a non-electrolyte. FT-IR spectra show that Schiff’s base and thiocyanate ion are coordinated to the metal ion in a monodentate manner. The electronic spectrum and the magnetic moment indicate the geometry of the complex is found to be distorted octahedral. The antimicrobial activities of ligands and their Fe(III) complex were studied against the few microorganisms by agar - well diffusion method. The complex shows moderate activity against the bacteria and enhanced activity against the fungi as compared to the SBPS ligand.